The slurry and physical-mechanical performance of autoclaved aerated concrete with high content solid wastes: Effect of grinding process. (10th September 2019) - Cai, Lixiong; Li, Xiangguo; Liu, Wenli; Ma, Baoguo; Lv, Yang
Highlights: Preparing HCS-AAC by utilizing more than 90% solid-wastes. Calcareous and siliceous solid wastes mix grinding process of HCS-AAC was proposed. The economical and environmental benefits of HCS-AAC were evaluated. Abstract: In high content solid-wastes autoclaved aerated concrete (HCS-AAC) preparation, the grinding process of raw materials have significant influence on the powder particle size which subsequently shows influence on the slurry uniformity and mechanical properties of HCS-AAC preparation. To clarify the effect of raw material fineness on HCS-AAC, influence of carbide slag and iron tailing fineness on slurry performance and physic-mechanical properties of HCS-AAC were investigated. Furthermore, according to the special raw material system of HCS-AAC, mix grinding process was proposed to promote pretreatment efficiency and slurry uniformity. Meanwhile, effect of mix grinding process on particles characteristics, slurry performance and physic-mechanical properties were discussed. Otherwise, economical and environmental benefits were analyzed to evaluate the environmental safety and social value of HCS-AAC products. The results indicated that raw material fineness has little influence on slurry foaming process. Meanwhile, with finer of iron tailing and carbide slag, the compressive strength of HCS-AAC were improve by 8–13%. Attributed to the non-hydration heat carbide slag, mix grinding technique was conducted to promote grinding efficient and improve compressive strength of HCS-AAC, which increased by 0.15–0.2 MPa than conventional divided grinding. The majority minerals in HCS-AAC were consist of calcium silicate hydrate (C-S-H) gel and tobermorite besides quartz and sluggishness minerals from raw materials. Additionally, HCS-AAC has significant benefits both in producing cost reduction and environmental conservation. This study provided a lower energy consumption technical route in preparation of high solid-wastes utilization, thermal insulation cellular construction material.